Thermophysical Properties of Concrete Blended with Iron Powder and/or Iron Fibers - Kanibou Fatima; Moufakkir Abdelkrim; Samaouali Abderrahim; Bakari Randa; Ouaazizi Karima; Arbaoui Asmae; Charkaoui Abdellah (Civil and Environmental Engineering, 2024)
The use of iron waste in concrete is now of considerable importance, mainly because of the benefits for the environment and for improving the strength of concrete. The increased and unused of this industrial byproducts represents a challenge for the environment and human health. This article experimentally explores the influence of utilizing iron powder waste and iron fibers in concrete in order to enhance the thermophysical properties of concrete and reduce the environmental impact resulting from iron waste. The aim of this work is to study the thermophysical properties (thermal conductivity, volumetric heat capacity, thermal diffusivity and thermal effusivity) of concrete with waste iron powder and iron fibers for application in building construction. The iron powder waste was added to the concrete with different percentages of 0%, 5%, 15%, 20% and 25% respectively as a partial replacement of sand. The iron fibers were added with mix proportions including 1.0%, 1.5%, 2.0% and 2.5% by volume of concrete, and in two different arrangements, uniform and random. The thermal conductivity and the volumetric heat capacity of these samples were measured experimentally in the dry state at ambient temperature (20 °C), and at 28 days of age. The effect of the integration of iron powder and fiber on thermal properties was analysed.